KEDUDUKAN HUKUM KREDITUR PEMEGANG HAK TANGGUNGAN PERJANJIAN KREDIT KAJIAN YURIDIS BERDASARKAN UNDANG-UNDANG No. 4 TAHUN 1996 TENTANG HAK TANGGUNGAN - Ulfah, Abidatul (JURNAL LEGISIA, 2021)
With the increasing increase in national development that focuses on the economic sector, with increasing development activities, the need for the availability of funds is also increasing, most of which are obtained through credit, one of the facilities that have a strategic role in procuring funds is banking institutions, in meeting the need for funds for economic activities. in the form of bank credit, and the enactment of Law number 4 of 1996 concerning mortgage rights over land and objects related to land, mortgages being the only institution to guarantee land rights, the presence of the UUHT cannot be separated from the situation and conditions of development in the field of land rights. an economy that requires large enough funds, so it requires a strong guarantee rights institution and is able to provide legal certainty for interested parties, what is the legal position of the creditor holding the mortgage if the debtor defaults in the credit agreement and the resolution of execution problems i Mortgage in practice, normative juridical research method to describe the legal certainty of mortgage guarantee in laws and regulations associated with the practice of its application, a debtor defaults and an unregistered mortgage right (APHT) deed, then the mortgage does not meet the principle of publicity and the principle of preference, but creditors still have the right to obtain collateral, only that their position is equal to other creditors. In the event of a violation or negligence of not registering the APHT to the land office by the PPAT or notary, the PPAT or Notary will be subject to administrative sanctions and the nature of the mortgage is to continue to follow the object in the hands of whoever the object. Keywords: Legal Position, Credit Agreement, Creditors holding mortgages